(3QSGdI aj CMcGe GdCOhjI GdbdHjIs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3bGd aUd Ef Gddg JYGdi Ndb GdJLhja GdCjSQ ef JLhjai GdbdH NRGfI ddQhM hNdb GdQhM eWjI ddbhi GdfaSGfjI s
(3BNQgG (B:s
(3cPdc agPG eG MVQfG ef GdcdGe ai GdCOhjI GdbdHjI Ydi CbUi eG jecf ef GdGNJUGQ hbO MGf dfG Cf JJe gPg GdebGdI s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdKGefIs
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B51s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs